Flavobacterium meningosepticum Colonization in Pediatric Intensive Care Unit - Antonius H. Pudjiadi (Indonesian Pediatric Society, 1999)
During a period of one month 2 infants was infected by Flavobacterium meningosepticum. The ages of the patients were 3 days and 5 months. The organisms were resistant to many antibiotics. The pathogens were isolated from the bronchial secretion and considered a nosocomial infection. The primary source of infection could not be identified. We suspect that the humidifiers or ventilators are the source of infections.